(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article presents information about one of the famous public and political figures of his time, Aidarbek uulu Eltoidu, who until that time was unknown in scientific publications. Information about Eltoidu Aidarbek uulu, who occupied an influential place in the palace and political life of the Kokond Khanate, and subsequently played a key role in the development of Asan uulu Alimbek-datka as a person and a state politician, has been preserved in the mouths of the people. Unfortunately, there is no information about this famous person in Russian-language sources. The reason is that in 1872, before the conquest of the Russians, Eltoidu died. On the basis of oral information collected in the Alay region, in Kokand we will tell about the life and work of Eltoidu Aidarbek uulu, who influenced the development of Alymbek-datka as a personality, statesman and political figure.